TEKNOLOGI INOVATIF PENGOLAHAN MAKANAN UNTUK PENINGKATAN KAPASITAS PRODUKSI UMKM DI KABUPATEN SIDOARJO - Amallia Puspitasari; Desi Erlita; Ucik Ika Fenti Styana (Institut Teknologi Dirgantara Adisutjipto, 2021)
Sidoarjo district is known as one of industrial center processed foods as chips cassava and shrimp crackers by UMKM Berkas Sejahtera. The high demand from the customers can not be covered because of the limitation of technology in production. Through this program is expected to partner businesses can increase the company production capacity, income and job opportunities for the community. Method used in this program is developing of efficient processed food production technology. Activities stages in this program were to identify real needs related production partner operational, designed and manufactured the production of processed foods effective, operational testing machine, evaluation machine, and intitutional strengthening and human resources. The output of this program are the package processing technology chips cassava and prawn crackers consist of cassava chopper, spinner, meat grinder, the hexagonal stirer seasoning, mixer the batter, press crackers,drying machine crackers and packaging machine. The results of the program is improving partner production capacity such that the program can be increasing from 1tons per day into 3 tons per day. So can increase income and job opportunities for the people in surrounding region.